Gender stereotyping, sex and violence in portuguese and spanish advertisement - Pereira, Francisco José Costa (2021)
The aim of this study is to demonstrate how gender stereotypes are materialised in advertisements, and how the use of sexual and violent contents can have discriminatory affects on women. We have conducted this study after ascertaining that gender stereotypes, as well as sexual and violent scenes, are embedded in advertisement as a formula to increase the likeness of remembering them. Our advertisement analysis explores gender stereotyping, sex and violence, both for the Portuguese and Spanish advertisement market. We used a sample of 245 messages from Portuguese and Spanish advertising. To his analyse, we used a specific grid. The main conclusions show us that advertisement in Portugal and Spain still have a significant amount of gender stereotypes, which is in agreement with other international studies. However, there were practically no situations of discrimination of women, placing them in subordinate roles to men.